A new approach to rapidly generate random periodic representative volume elements for microstructural assessment of high volume fraction composites. (15th July 2018) - Li, Geng; Sharifpour, Farzad; Bahmani, Aram; Montesano, John
Abstract: An algorithm based on event-driven molecular dynamics theory was developed to rapidly generate periodic representative volume elements (RVEs) with nonuniform distributions for both unidirectional fibre-reinforced and spherical particle-reinforced composites. Detailed statistical analyses were conducted for assessing the ability to generate RVEs with nonuniformly dispersed microstructures and either constant or random inclusion sizes for a wide range of volume fractions. The generated microstructures were directly compared with available microstructural optical images of a composite material, showing excellent statistical correlation and providing validation for the developed RVE generation approach. For further validation, finite element analysis was conducted using the generated RVEs in order to evaluate volume averaged elastic constants. The expected isotropic characteristics of the RVEs were correctly calculated, and excellent correlations with experimental data from the literature provided additional support for the algorithm accuracy. The versatile algorithm can rapidly generate RVEs with realistic reinforcement dispersions and high volume fractions up to 80%, which is advantageous compared to other algorithms. The proposed algorithm can be used as a design tool to accurately evaluate and tailor the mechanical properties of distinct composite material systems, and for their microstructural assessment including local damage predictions. Graphical abstract: Highlights: New method rapidly generates RVEs with nonuniform reinforcement dispersion for high Vf UD fiber and particulate composites Statistical assessment of RVE reinforcement dispersions are validated by comparison with real composite microstructures RVEs with volume fractions up to 80% were rapidly generated without convergence issues Volume averaged elastic constants calculated via computational FEA, with excellent correlation to experimental data Developed algorithm can be used as design tool to accurately evaluate and tailor properties of distinct composite materials